Nigeria's 36 states and the FCT : economic, fiscal, sectoral, and wellbeing profiles (Lagos, Nigeria : Economic Associates, 2010)
Underlines that Nigerian states have enormous scope for competition to secure inward investment.
Vol.1. A-TO-Z; Vol.2. At -A-Glance; Vol. 3: Regional Insights
March 2012 Issue has 3 volumes
oif 03/12/14
Ref
Keywords: Economic Conditions -- Nigeria; Economic developmentzNigeria; nvestments -- Nigeria; Nigeria -- Economic situation